2013
DOI: 10.1111/imb.12070
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA levels are modulated in Aedes aegypti after exposure to Dengue‐2

Abstract: To define microRNA (miRNA) involvement during arbovirus infection of Aedes aegypti, we mined deep sequencing libraries of Dengue type 2 (DENV2) -exposed mosquitoes. Three biological replicates for each timepoint (2, 4, and 9 days post-exposure (dpe)) and treatment group allowed us to remove outliers associated with sample-to-sample variability. Using edgeR (R Bioconductor), designed for use with replicate deep sequencing data, we determined the log fold-change (logFC) of miRNA levels (18–23 nts). The number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
89
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 50 publications
(95 reference statements)
6
89
0
1
Order By: Relevance
“…A number of differentially expressed miRNAs have been identified in DENV-infected A. aegypti cells (48). Targets of these miRNAs include genes responsible for transcription regulation, mitochondrial function, intracellular transport, chromatin modification, and signal transduction that are known to be required for viral replication and dissemination (48). In the present study, we identified a novel mechanism of antiviral response in insects that is dependent on a host miRNA.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…A number of differentially expressed miRNAs have been identified in DENV-infected A. aegypti cells (48). Targets of these miRNAs include genes responsible for transcription regulation, mitochondrial function, intracellular transport, chromatin modification, and signal transduction that are known to be required for viral replication and dissemination (48). In the present study, we identified a novel mechanism of antiviral response in insects that is dependent on a host miRNA.…”
Section: Discussionmentioning
confidence: 71%
“…Specifically, WNV infection of human cells was shown to induce the expression of miRNA hsa-miR-154, which downregulates the expression of antiapoptotic proteins CCCTCbinding factor and EGFR-coamplified and overexpressed protein, thus inducing apoptosis in infected cells (30). A number of differentially expressed miRNAs have been identified in DENV-infected A. aegypti cells (48). Targets of these miRNAs include genes responsible for transcription regulation, mitochondrial function, intracellular transport, chromatin modification, and signal transduction that are known to be required for viral replication and dissemination (48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dengue virus (DENV) infection was shown to alter the expression of numerous miRNAs in mosquito (18) and human (19) cells. In particular, DENV strongly induced the expression of miR-146a in human monocytes, with significant benefit to virus replication (20).…”
mentioning
confidence: 99%
“…Differential expression of host miRNAs has been shown for baculoviruses [28,29,30 ], an ascovirus [31], a cytoplasmic polyhedrosis virus [32], West Nile virus (WNV) [33 ], chikungunya virus [42] and dengue virus (DENV) [34]. These changes, detected by microarray or deep sequencing analyses, could be either due to host response to viral infection or host manipulation by the virus, including virusencoded miRNAs (see below).…”
Section: Introductionmentioning
confidence: 99%